Comparative study of ultrasonographic, hysteroscopic and histopathological findings in patients with abnormal uterine bleeding - Wani, Iram; Ain, Syed Najmul; Chalkoo, Jabeena Ali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: AUB (Abnormal uterine bleeding) is a considerable health care burden not only for women but their families and has a definite effect on their quality of life. Objective was to compare the ultrasonographic, hysteroscopic and histopathological findings in patients with abnormal uterine bleeding. Methods: This prospective observational study was conducted at the department of obstetrics and gynecology, Indraprastha Apollo Hospital, New Delhi, from July 2018 to June 2019. The women who came to the OPD with the complaint of AUB in the one year period and met the eligibility criteria were taken for the study. TVS was performed in 126 patients presenting with complaints of abnormal uterine bleeding followed by hysteroscopic biopsy or curettage. The specimens were sent for histopathologic examination. Results: Mean age was 43.95±8.48 years. Most common presenting complaint was found to be menorrhagia (n=53; 42%) followed by post-menopausal bleeding (n=30, 24.0%). The mean endometrial thickness was 9.79±4.84 mm. The diagnostic specifications of TVS taking histopathological examination as gold standard were: sensitivity = 64/77= 83.1%, specificity 39%, positive predictive value 68%, negative predictive value 59% and accuracy 66%. Hysteroscopy has a sensitivity of 87%, specificity of 51%, positive predictive value of 74%, negative predictive value of 71.4% and diagnostic accuracy of 73% in diagnosing aetiology of abnormal uterine bleeding. Conclusions: Both TVS and hysteroscopy are good diagnostic modalities for investigation of AUB. However, hysteroscopy has an edge over TVS in diagnosing aetiology of AUB in terms of high sensitivity, specificity and negative predictive value.